Green Economics Model in Non-Organic Waste Management in Tegal Tugu Village, Gianyar - Ngakan Made Adi Satria; I Kadek Andika Putra; Kadek Fajar Arisudana; I Gede Arinata Putra (Lembaga Penelitian, Universitas Warmadewa, 2025)
This study aims to analyze the application of the green economics model in the management of inorganic waste in Tegal Tugu Village, with a focus on the economic and environmental impacts produced. The increasing amount of inorganic waste that is not managed properly has the potential to damage the environment and burden the final disposal site. Through the green economics approach, which prioritizes the reuse and processing of waste into valuable items, it is hoped that a more sustainable solution can be created. The method used in this study is a qualitative descriptive approach with data collection through interviews, observations, and literature studies. The results of the study indicate that the application of green economics in Tegal Tugu Village can reduce the volume of waste entering the landfill, increase household income, and reduce negative impacts on the environment. However, the challenges faced include the lack of public awareness and limited supporting infrastructure. This study suggests the importance of continuous education and strengthening cooperation between the government, community, and private sector.